2017
DOI: 10.1021/acs.iecr.7b02369
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Alkyl Amine Surfactants in Mixed Gas and Pure CO2 Environments

Abstract: This study analyzes the changes in solubility and mass distribution of three alkyl amine surfactants in pure, supercritical carbon dioxide (ScCO2) and in supercritical carbon dioxide–methane (ScCO2–ScCH4) mixtures under high-pressure conditions at 40 or 60 °C. It was observed that highly methylated surfactant structures have the highest solubility in ScCO2, up to 1 wt % at 40 °C, and exponentially declined with addition of methane in the system. Moreover, methylated surfactant structures with lower molecular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…19,28,30 However, the P c was usually reported to increase with temperature for the surfactants in literature, which include trimethyl-nonyl-(ethylene oxide) n (noted as b-C12-EOn), nonyl-phenol-(ethylene oxide) n (noted as NP-EOn), 2-ethyl-hexanol-(ethylene oxide) n -(propylene oxide) m (noted as b-C8-EOn-POm), alkyl ethoxylated amines (noted as C12-14-EOn-A), and alkyl ditertiary-amine (noted as C16-18-DTA). 19,[28][29][30]34,36 The comparison of C8-16-DA with the surfactants in literature for the P c is shown in Figure 7. Therefore, the surfactants in literature require a higher pressure for dissolving in CO 2 at higher T, which may restrain their application in the hot reservoirs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…19,28,30 However, the P c was usually reported to increase with temperature for the surfactants in literature, which include trimethyl-nonyl-(ethylene oxide) n (noted as b-C12-EOn), nonyl-phenol-(ethylene oxide) n (noted as NP-EOn), 2-ethyl-hexanol-(ethylene oxide) n -(propylene oxide) m (noted as b-C8-EOn-POm), alkyl ethoxylated amines (noted as C12-14-EOn-A), and alkyl ditertiary-amine (noted as C16-18-DTA). 19,[28][29][30]34,36 The comparison of C8-16-DA with the surfactants in literature for the P c is shown in Figure 7. Therefore, the surfactants in literature require a higher pressure for dissolving in CO 2 at higher T, which may restrain their application in the hot reservoirs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Liebum et al [100] tested the solubility of three alkylamine surfactants in scCO 2 and supercritical carbon dioxide-methane mixture (scCO 2 -scCH 4 ) under high-pressure conditions at 40 • C and 60 • C. It was observed that highly methylated surfactant structures had the highest solubility in scCO 2 , up to 1 wt% at 40 • C, and the solubility decreased exponentially with the addition of methane to the system. Because of the strength of the surfactant-scCO 2 intermolecular interaction, the scCO 2 preferred shorter tail groups.…”
Section: Hydrocarbon Surfactantsmentioning
confidence: 99%
“…Meanwhile, an apparent free gas phase will increase with the vaporization of an oleic lighter component into ScCO 2 . This CO 2 phase composition change would directly cause the reduction of CO 2 -soluble surfactant partition coefficients 68 and variation of foam apparent viscosity. 69 On the contrary, the decrease of the free gas phase during the condensing process could reduce the delivery efficiency of CO 2soluble surfactants and apparent foam viscosity, which is equivalent to suppress the spreading effect.…”
Section: Sensitivity Studies 231 Spreading Effect Caused Bymentioning
confidence: 99%